Investigating the utilization of biomaterials and bioengineering methods in developing functional cardiac tissue for heart repair - Omar Elsaka (MGM Journal of Medical Sciences)
It has become increasingly apparent that cardiac tissue engineering applications can be employed to repair heart injuries. The primary purpose of the present research is to examine the use of biomaterials and bioengineering methods to create functioning cardiac tissue. Techniques for tissue maturation, scaffold design, cell sources, and biomaterial selection are important subjects. The proper growth of functioning heart tissue is dependent upon these factors. The assessment emphasizes further research and development areas and discusses the field’s challenges and potential solutions. In conclusion, this article highlights the significant advancements in cardiac tissue engineering. Regardless of its challenges, the medical discipline of cardiology has left tremendous prospects for heart repair in future generations. In this significant progress in this critically important area of regenerative medicine, biomaterials, bioengineering research, and innovation are necessary.